Study of TRAF3IP3 for prognosis and immune infiltration in hepatocellular carcinoma - Wang, Xing; Gao, Xin; Liu, Airu; Qin, Yan; Ni, Zhi-Yu; Zhang, Xiao Lan (PeerJ, 2024)
Background Tumor necrosis factor receptor-associated factor 3 (TRAF3)-interacting protein 3 (TRAF3IP3) expressed in various tumor cell. However, its role in hepatocellular carcinoma (HCC) was unclear. We aimed to demonstrate the relationship between TRAF3IP3 and HCC and explore the potential role of TRAF3IP3 in HCC. Methods The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO), Genotype-Tissue Expression (GTEx), KM-Plotter, University of Alabama at Birmingham Cancer data analysis Portal (UALCAN), and Xiantao Academic Online Website were utilized for the systematic analysis of TRAF3IP3. This analysis included mRNA expression, protein expression, prognostic value, enrichment analysis, and immune cell infiltration in HCC. Subsequently, immunohistochemistry was performed to assess the expression levels of TRAF3IP3 in both cancer and non-cancer tissues of patients with HCC. Results Analysis of public databases and immunohistochemical staining on 20 pairs of samples confirmed a decrease in TRAF3IP3 expression in HCC. Both the TCGA database and GSE14520 indicated that patients with high TRAF3IP3 expression had a more favorable prognosis in terms of overall survival (OS) and progression-free interval (PFI), as shown by KM curve results. Multivariate Cox regression analysis further demonstrated that high TRAF3IP3 expression was an independent protective factor for HCC prognosis (hazard ratio (HR): 0.619, 95% confidence interval (CI) [0.399–0.959]; p < 0.05). In the high TRAF3IP3 expression group, various immune response-related molecular pathways, particularly B lymphocyte-mediated pathways, were activated. The level of TRAF3IP3 expression showed a significant correlation with the presence of tumor-infiltrating CD8+ T cells. Additionally, a positive correlation was observed between immunophenoscore (IPS) and TRAF3IP3 expression. Notably, the half-maximal inhibitory concentration (IC50) of commonly used chemotherapeutic drugs, such as lapatinib and mitomycin, was inversely associated with TRAF3IP3 expression in HCC patients. Conclusion TRAF3IP3 may be as a novel and promising biomarker for prognosis prediction and immunological evaluation of HCC.
Keywords: TRAF3IP3; Lymphocyte; Immune cell infiltration; Hepatocellular carcinoma; Immunotherapy; CD8+ T cells; Biomarker; Prognosis; CTLA-4; PD-1